Case Report: Congenital Brain Dysplasia, Developmental Delay and Intellectual Disability in a Patient With a 7q35-7q36.3 Deletion - Fan, Liang-Liang; Sheng, Yue; Wang, Chen-Yu; Li, Ya-Li; Liu, Ji-Shi (Frontiers in Genetics, 2021)
7q terminal deletion syndrome is a rare condition presenting with multiple congenital malformations, including abnormal brain and facial structures, developmental delay, intellectual disability, abnormal limbs, and sacral anomalies. At least 40 OMIM genes located in the 7q34-7q36.3 region act as candidate genes for these phenotypes, of which SHH, EN2, KCNH2, RHEB, HLXB9, EZH2, MNX1 and LIMR1 may be the most important. In this study, we discuss the case of a 2.5-year-old male patient with multiple malformations, congenital brain dysplasia, developmental delay, and intellectual disability. A high-resolution genome-wide single nucleotide polymorphism array and real-time polymerase chain reaction were performed to detect genetic lesions. A de novo 9.4 Mb deletion in chromosome region 7q35-7q36.3 (chr7:147,493,985-156,774,460) was found. This chromosome region contains 68 genes, some of which are candidate genes for each phenotype. To the best of our knowledge, this is a rare case report of 7q terminal deletion syndrome in a Chinese patient. Our study identifies a rare phenotype in terms of brain structure abnormalities and cerebellar sulcus widening in patients with deletion in 7q35-7q36.3.